HUKUM PIDANA, DEMOKRASI DAN HAM - Didik Endro Purwoleksono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
Speaking of law is always connected with democracy and human rights as an integrated component. Law is described as a frame or legalization of democracy, while democracy it self is a part of human rights, furthermore, human rights need to be constructed as a specific law.